2002
DOI: 10.1159/000063303
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia in Wegener’s Granulomatosis

Abstract: Background: Significant lymphopenia is a prominent feature in systemic erythematous lupus, but has not been described in Wegener’s granulomatosis (WG). We suggest from a retrospective analysis that lymphopenia may also be an index of WG disease activity. Methods: Medical charts form 19 patients diagnosed with systemic active WG between 1990 and 2000 were reviewed retrospectively. All patients had crescentic glomerulonephritis and alveolar hemorrhage. Clinical and biological markers were reviewed at three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In line with earlier observations, we found that patients with AAV had a decreased percentage of lymphocytes and an increase of PMN. Low levels of lymphocytes are common on diagnosis of AAV and during flares [ 33 ] and might also be an effect of immune suppressive treatment [ 34 , 35 ]. The increased percentage of PMN in patients with AAV could be explained by increased survival in the periphery in combination with elevated bone marrow release.…”
Section: Discussionmentioning
confidence: 99%
“…In line with earlier observations, we found that patients with AAV had a decreased percentage of lymphocytes and an increase of PMN. Low levels of lymphocytes are common on diagnosis of AAV and during flares [ 33 ] and might also be an effect of immune suppressive treatment [ 34 , 35 ]. The increased percentage of PMN in patients with AAV could be explained by increased survival in the periphery in combination with elevated bone marrow release.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that treatment-induced lymphopenia (·0.5 £ 10 9 /L) is associated with a high likelihood to achieve sustained remission [3,7]. By contrast, another group suggested that, analogous to patients with systemic lupus erythematodes, lymphopenia in AAV reXects disease activity, with lymphocyte counts actually increasing in patients achieving remission [8,9]. While the reason for these contradictory Wndings remain unclear, neither study has taken into account short-term variability of lymphocyte counts and how this might impact study results.…”
Section: Introductionmentioning
confidence: 99%